Social Control and Legal Reform: A Study of Minimum Marriage Age From the Perspective of Islamic Law and Plural Legal Systems - khaliq, Munawwir; Muhasim, Ahmad; Sado, Arino Bemi; Azman Ab Rahman (KALOSARA: Family Law Review, 2025)
Although numerous studies have examined the practice of child marriage in Indonesia, few have analyzed this phenomenon from the perspective of legal pluralism, which encompasses state law, customary law, and religious law. This study aims to analyze child marriage within the context of legal pluralism in Indonesia, focusing on the coexistence of state, customary, and religious norms regulating marriage and their influence on child protection policies. The study employs a qualitative approach with a literature review design and thematic analysis to achieve this objective, integrating the theories of maslahah mursalah, social control, and legal pluralism. Through this analysis, the study explores how legal regulations governing the minimum age of marriage often conflict with prevailing social and religious norms, and how practices such as unregistered marriage (nikah sirri) and marriage dispensations continue despite formal regulations. The findings suggest that, although legal frameworks exist, their implementation is still constrained by strong social and cultural norms. Therefore, a holistic policy approach is required, involving social education and community empowerment to reshape perceptions of child marriage and strengthen law enforcement. This study contributes to the understanding of legal pluralism in child marriage and provides recommendations for more effective and contextually appropriate child protection policies. Keywords: Islamic Law, Minimum Marriage Age, Plural Legal System